Battery hazards and safety: A scoping review for lead acid and silver-zinc batteries. (August 2021) - Schismenos, Spyros; Chalaris, Michail; Stevens, Garry
Highlights: Battery safety, health and environmental information reviewed. Detailed comparison between lead acid and silver-zinc batteries. Battery fire awareness can minimize risks and prevent fire incidents. Abstract: Batteries play a critical role in our lives. However, depending on their chemical compositions and contents, they may turn into serious threats for both humans and the environment. Misuses and high temperatures during the operations may result in cell cracks and release hazardous liquids and gasses. In order to prevent fire ignition, strict safety regulations in battery manufacturing, storage and recycling facilities should be followed. This scoping review presents important safety, health and environmental information for lead acid and silver-zinc batteries. Our focus is on the relative safety data sheets and research studies. All findings are explained in a simple and clear manner. The goal of this paper is to identify risks and recommend solutions appropriately designed for increasing battery fire awareness.